Different Influences on Lautering Performance and Wort Quality Attributes when Brewing with 100 % Unmalted Barley - Nsogning Dongmo, Sorelle; Zarnkow, Martin; Becker, thomas (BrewingScience, 2013)
The use of wort from unmalted barley in beer production offers many challenges to the brewers. The experimental data summarized in this paper aims to examine the influence of grist quality of two unmalted barley varieties on mash filterability and some wort quality attributes when brewing with 100 % unmalted barley. Milling settings (four-roller mill, six-roller mill and hammer mill), barley conditioning and two barley varieties were considered. First of all, seven series of grits of varying quality from two varieties (Beatrix and 2300/Irlbach) were produced with various milling settings, and conditioning. Mashing was carried out following a specific mashing program. Enzymes consisting of α-amylase, β-glucanase/arabinoxylanase, protease, pullulanase and lipase were provided by Novozymes. The influence of grist quality, and variety on mash lautering efficiency and the quality of the resultant wort were investigated.